2019
DOI: 10.3122/jabfm.2019.06.190115
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Characterization of Yoga Mentions in the Electronic Health Record

Abstract: Background: There is a growing patient population using yoga as a therapeutic intervention, but little is known about how yoga interfaces with health care in clinical settings. Purpose: To characterize how yoga is documented at a large academic medical center and to systematically identify clinician-derived therapeutic use cases of yoga. Methods: We designed a retrospective observational study using a yoga cohort (n ‫؍‬ 30,976) and a demographically matched control cohort (n ‫؍‬ 92,919) from the electronic hea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…During the study period there were approximately 1.2 million patients in the database, 2–3% of which had at least one clinical chart note containing the word “yoga” [ 14 ]. Available structured data fields include demographics, clinical encounters, diagnostic and procedure codes, laboratory test results, and prescribed medications.…”
Section: Methodsmentioning
confidence: 99%
“…During the study period there were approximately 1.2 million patients in the database, 2–3% of which had at least one clinical chart note containing the word “yoga” [ 14 ]. Available structured data fields include demographics, clinical encounters, diagnostic and procedure codes, laboratory test results, and prescribed medications.…”
Section: Methodsmentioning
confidence: 99%
“…As a reflection of the above, a study of electronic health records (EHR) at Penn Medicine between 2006 and 2016 found a tenfold increase in the prescribing of yoga as a treatment modality by primary care physicians for a range of musculoskeletal conditions such as lower back pain, myalgia and myositis [ 59 ]. This could signal an already increasing acceptance of yoga as a therapeutic intervention.…”
Section: Benefits Of Yoga On Painmentioning
confidence: 99%